Around "Deconstruction." Author’s Response - David J. Gunkel (Studia Philosophiae Christianae, 2023)
In this paper I reply to the four critical articles that were provided in response to my book Deconstruction (MIT Press 2021). It proceeds in four steps: (1) I begin with a reply to Stanisław Chankowski’s use of the psychoanalytic term “fetishistic denial” to describe the formal character of the text. (2) I then engage with the criticism supplied by Piotr Kozak, who questions deconstruction’s theory of truth (or its lack thereof). (3) From this, I take-up and respond to Przemysław Nowakowski’s proposal that deconstruction might provide a way to reimagine the interdisciplinarity of cognitive science. And (4) I conclude with a response to Michał Piekarski’s mashup of Ludwig Wittgenstein and Jacques Derrida, which supplies a reading of these two thinkers that is arguably greater than the sum of the parts. The objective of the reply is not to offer a defense of myself or my text but to engage with these interesting and insightful reviews in a way that opens the space for productive dialogue.